Redeeming Grace - Durham, Weldon B.
It is 1912 and Grace Lampley has returned to St. Louis to work as a clerk in a real estate office. Ever wary of romance, she enjoys a single life in the city's parks, nickelodeons and dance halls. That is, until she meets Ray, who has come out from New York to manage a new theatre. She is captivated by his tenderness and sweetness and awed by the glamorous company he keeps, so she accepts his proposal of marriage. Grace's demons of self-doubt nearly destroy the marriage, but it survives a move to New York. Ray is promoted and Grace goes to work for theatre mogul, Jacob J. Shubert. Her world explodes with excitement and she gradually emerges to full awareness of her strength and identity. She also begins to recognize her hidden desires and to act on them. Grace and Ray blossom until war separates them. Will the war end soon enough?